2017
DOI: 10.2196/jmir.6676
|View full text |Cite
|
Sign up to set email alerts
|

MyGeneFriends: A Social Network Linking Genes, Genetic Diseases, and Researchers

Abstract: BackgroundThe constant and massive increase of biological data offers unprecedented opportunities to decipher the function and evolution of genes and their roles in human diseases. However, the multiplicity of sources and flow of data mean that efficient access to useful information and knowledge production has become a major challenge. This challenge can be addressed by taking inspiration from Web 2.0 and particularly social networks, which are at the forefront of big data exploration and human-data interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Thus, a whole system of quasi-dynamic ODEs (2) can inform us of the numbers of outgoing links and incoming links for each gene. According to network theory, this information allows us to classify all genes into hub (core) genes and peripheral genes, leader genes and subordinate genes, or social genes and solitary genes (Allot et al, 2017). We argue that core genes may not necessarily display a strong intrinsic capacity of expression by which to affect network behavior and function.…”
Section: Optimizing the Topological Structure Of Grnsmentioning
confidence: 95%
“…Thus, a whole system of quasi-dynamic ODEs (2) can inform us of the numbers of outgoing links and incoming links for each gene. According to network theory, this information allows us to classify all genes into hub (core) genes and peripheral genes, leader genes and subordinate genes, or social genes and solitary genes (Allot et al, 2017). We argue that core genes may not necessarily display a strong intrinsic capacity of expression by which to affect network behavior and function.…”
Section: Optimizing the Topological Structure Of Grnsmentioning
confidence: 95%
“…A panoply of services and apps is available to create, collect and share different types of data. 38,39 Data may originate from clinical records, current or ad hoc data flows (e.g. registries of pathology, claims data, etc.…”
Section: Distributed Ledger Technologies Supporting the Data Process In Scientific Researchmentioning
confidence: 99%
“…As a consequence, digital technologies, tools, and services became a core component of both Healthcare Management and scientific Research (HMR), as confirmed by the WHO guideline and recommendations on digital interventions for health system strengthening (2). Particularly, HMR is increasingly adopting digital tools that allow data to be shared between geographically distant subjects (3)(4)(5)(6)(7). Data interoperability, security, privacy and ease of sharing are core components of high quality HMR.…”
Section: Introductionmentioning
confidence: 99%
“…Data interoperability, security, privacy and ease of sharing are core components of high quality HMR. A panoply of solutions is already available to create, collect and share different types of data (6)(7)(8)(9) originating from different sources (clinical records, current or ad hoc data streams, directly from patients or published studies).…”
Section: Introductionmentioning
confidence: 99%